A complexa teia do novo historicismo: percursos e contribuições para a escrita da história - Arantes, Cristiane Paula (2022)
The present doctoral thesis seeks to understand what is the place of the proposal of new historicism to reflect the changes and challenges of the historian's activity in its various approaches and fields of research in the history of historiography. To this purpose, we seek to establish an analysis of classical historicism and new historicism in order to understand which are their particular paths and characteristics. We tried to trace the path of emergence of new historicism by situating it to understand if it was a movement and what it brings as new, since it deals with how the work of art can be understood, especially literature, as well as historical narrative, its function, methodology and style. Our methodology consisted of developing a discussion of the changing regime of historicity and historiography to demonstrate the fundamental concepts of classical historicism and new historicism from documentary, digital sources and classical texts. We then build up the fundamental concepts of the new historicism, its targets of criticism, its sayings, unsaid, and considerations. The analysis of the main themes of the new historicism was built from an empirical research with articles from the journal Representations in the period between 1983 and 1999, this approach was possible through a lexical analysis executed by the software Iramuteq. Subsequently, we presented a more qualitative verification of the collection of articles with a more vertical approach on some texts, so that it could exemplify how the main themes appear in the magazine. This allowed a more careful apprehension to understand how and if the issues of the journal Representations contributed to the dissemination and fixation of the new historicist canon. In addition to working with the journal, we mobilized other sources such as interviews with the founding members of the journal, images, and other digital discourses in order to conclude whether the proposal of new historicism was ventured from a movement, or whether it was only a trend of reading and writing practices. Finally, we develop a reflection on the possible contributions of the new historicism to historiography.